Detecting the magical yellow-blue demarcation off the Yellow River Estuary from the space - Li, Peng; Chen, Shenliang; Ji, Hongyu; Fan, Yaoshen; Fu, Yutao; Ran, Baichuan; Ke, Yinghai (Frontiers in Marine Science, 2023)
River deltas rank among the most ecologically and socio-economically valuable environments on the planet. The Yellow River Delta in China is not only home to young wetland ecosystem, but also to world-renowned tourism resources. One of these was the unique yellow-blue demarcation line (YBDL), formed in the Yellow River Estuary (YRE) as a result of the meeting of terrestrial sediment-laden river water and clear sea water, which had developed into a famous attraction and generated significant tourism revenues. Moreover, its distribution was of vital ecological and geomorphological importance due to association with the dynamics of estuarine turbidity plume. However, little is yet known about the dynamics and influencing factors of YBDL. In this study, we proposed an integrated method for extracting YBDL from satellite imagery and investigated the spatiotemporal distributions of YBDL during the flood season (June-October) from 2016 to 2022 using multi-source satellite imageries. The average relative error of our algorithm reached 10.53%. The results indicated that the YBDL started to frequently occur after 2018, mainly distributed within 10 km off the YRE, with two types of short straight and long curved shapes. July was the period with the highest frequency and most widespread distribution of YBDL. The riverine water and sediment discharge controlled 45.9% of the variations in YBDL length, and the extreme flooding, as well as the implementation of Water-Sediment Regulation Scheme, significantly increased the distribution extent of the YBDL. The morphology of river distributary mouths dominated the changes in the YBDL distribution centres, and the north distributary mouth experienced dramatic evolution in the last three years, with an increased YBDL distribution. Tidal currents could promote the development of YBDL at the front of the river mouth plumes while inhibiting the YBDL on the other side. This study is the first systematic investigation of the spatiotemporal evolutions and driving mechanisms of YBDL in the YRE, which could provide a reference for tourism planning and YRE National Park construction.